Language Style in Ahla Khabar Poem By Nizar Qabbani - Rahmi, Hafizatur; Ermiş, Hamza (NALAR, 2025)
This article analyses the form and style of Nizar Qabbani’s language in his poem “Ahla Khabar” (The Most Beautiful News). This poem is known for its rich visual imagery, symbols, and influential figures of speech, making it an ideal object for stylistic analysis. The method used is a descriptive, qualitative approach, based on library research, to examine literary sources and analyse the poem’s language style in depth. The analysis shows that Nizar Qabbani uses several stylistic techniques, including hyperbole, personification, and repetition. Hyperbole is used to express the intensity of the poet’s love, which transcends the boundaries of the real world. Personification brings the universe to life. Repetition serves to emphasize the message, strengthen the intensity, and create a beautiful poetic rhythm, showing that the confession of love is written everywhere. Overall, these stylistic devices not only beautify the poem but also play an important role in constructing meaning, strengthening emotional expression, and conveying the poetic message about the depth, universality, and eternity of love.